Malacca Tourism WAP Portal - Zolkeply, Adrina (Universiti Teknologi Petronas, 2006)
Tourism sector is a leading revenue generator and an umbrella industry in Malaysia. Malacca has been chosen as the scope of study because tourism industry in Malacca has experienced a rapid and continuous growth. Nowadays, time is considered as valuable as gold. Once time is used sensibly, access to a lot of information is possible. Currently, tourists visiting Malacca having problem to search for information using paper maps. Important information such as available transportation (bus number, taxi phone number, fare), distance form one place to another place are not available in paper maps. This is because paper maps are only able to show limited information mainly determined by the map size. Tourists who want to go sightseeing in different places may need this information to plan their travel. Therefore, Malacca Tourism WAP Portal aims to ease tourists to find information about places of interest and sightseeing in Malacca using hand phone in connection with WAP service. This project covers two main areas which are GIS in tourism and WAP Based GIS. The realization of Malacca Tourism WAP Portal starts when user accesses the application and make request. Thgj-equest will be processejLbyJfacjsgebserver and MySQL.^ The result wjll be sent back to user and is displayed on the jphone screen. As a conclusion, Malacca Tourism WAP Portal aim to benefit tourists by providing essential information about tourism places in Malacca. Tourists can find information regarding tourism places (address, open hour, etc.), nearest hotel to stay and also travel information which includes available transportation, distance and others. This become as an alternative way to get information and beside that can assist them to make decision during their visit in Malacca.